A randomized clinical trial: timing of indwelling urethral catheter removal following transurethral resection of prostate - Saddam Al Demour; Mohammad T Al-Zubi; Mera Ababneh; Samer F Al-Rawashdah; Muayyad Ahmad (Future Science OA, 2023)
Aim: We aimed to evaluate early versus delayed removal of the indwelling urethral catheter (IUC) following transurethral resection of prostate (TURP). Methods: In this clinical trial conducted between July 2016 and June 2020, 90 patients underwent TURP were randomized equally into: group A, early IUC removal (24 h), and group B, delayed IUC removal (72 h). Results: The mean length of hospital stay was longer among the patients in group B. There were no significant differences in recatheterization, secondary bleeding, or UTI between groups A and B. The mean VAS score and CRBD were higher in group B. Conclusion: Early IUC removal following TURP is safe approach with favorable clinical outcomes. Clinical Trial Registration: NCT04363970 (clinicaltrials.gov)